Mathematical Analysis With Applications : In Honor of the 90th Birthday of Constantin Corduneanu, Ekaterinburg, Russia, July 2018 /: In Honor of the 90th Birthday of Constantin Corduneanu, Ekaterinburg, Russia, July 2018. (2020) - Unknown
No abstract available